2012
DOI: 10.1371/journal.pone.0040087
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown of Mucin as Barrier to Digestive Enzymes in the Ischemic Rat Small Intestine

Abstract: Loss of integrity of the epithelial/mucosal barrier in the small intestine has been associated with different pathologies that originate and/or develop in the gastrointestinal tract. We showed recently that mucin, the main protein in the mucus layer, is disrupted during early periods of intestinal ischemia. This event is accompanied by entry of pancreatic digestive enzymes into the intestinal wall. We hypothesize that the mucin-containing mucus layer is the main barrier preventing digestive enzymes from contac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
93
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(96 citation statements)
references
References 49 publications
3
93
0
Order By: Relevance
“…The present study demonstrated that FAK suppressed trypsin-induced cell detachment, and lysosome inhibitor NH 4 Cl suppressed cell detachment through mono-ubiquitination of FAK, while Cbl-b promoted cell detachment through ubiquitination of FAK. These results provide novel insights into the role of Cbl-b and FAK in cell detachment.…”
Section: Introductionsupporting
confidence: 52%
See 4 more Smart Citations
“…The present study demonstrated that FAK suppressed trypsin-induced cell detachment, and lysosome inhibitor NH 4 Cl suppressed cell detachment through mono-ubiquitination of FAK, while Cbl-b promoted cell detachment through ubiquitination of FAK. These results provide novel insights into the role of Cbl-b and FAK in cell detachment.…”
Section: Introductionsupporting
confidence: 52%
“…3A). In the NH 4 Cl-pretreated group, FAK degradation was suppressed compared with the control (Fig. 3B).…”
Section: Ubiquitin-lysosome Degradation Mediates Trypsin-induced Degrmentioning
confidence: 86%
See 3 more Smart Citations